Pengaruh Senam Tai-Chi Terhadap Tekanan Darah Pada Lansia Penderita Hipertensi di Posyandu Lansia Nusa Indah 7 Desa Cemani - Muttaqin Nur FahleviFahlevi, Wildan; Nasrul Sani, Fakhrudin; Wahyudi, Totok (Jurnal Pustaka Keperawatan (Pusat Akses kajian Keperawatan), 2026)
Hypertension is a non-communicable disease that can cause serious complications such as stroke and heart failure, especially in older adults. According to the Indonesian Health Survey, the prevalence of hypertension is quite high throughout Indonesia, including in the Sukoharjo area. Non-pharmacological management, such as Tai-Chi is quite effective because it is light aerobic and can reduce stress and improve cardiovascular function. The purpose of this study was to determine the effect of Tai-Chi on blood pressure of elderly people with hypertension in Posyandu Nusa Indah 7. The research methodology used a pre-experimental design with a one group pre-test and post-test design. A total of 31 elderly respondents were selected using total sampling. Three times a week. Data analysis was performed using the paired t-test statistical test. The findings showed that there was a significant decrease in systolic and diastolic blood pressure after Tai-Chi intervention (p < 0.05). This indicates that Tai-Chi is effective in reducing blood pressure in hypertensive elderly. This study highlights the importance of using non-pharmacological interventions, such as Tai-Chi, in elderly health programs, both as a treatment for hypertension and as a preventive measure.